ANALYSIS OF DNA SEQUENCE ENCODING GLYCERALDEHYDE-3-PHOSPHATE DEHYDROGENASE (GAPDH) ON COCOR BEBEK (KALANCHOE x LAETIVIRENS) - Putri Agustina; Dewi Indriyani Roslim (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
To understand the fundamental mechanisms on genes in plant cells can be performed by gene expression studies. The study needs reference genes that act as internal control to avoid expression data bias. Glyceraldehyde-3-Phosphate Dehydrogenase (GAPDH) gene is one of reference genes that has been validated in plants. This study aims to analyze the DNA sequences encoding GAPDH in cocor bebek (Kalanchoe x laetivirens). Methods included total DNA extraction from fresh leaf, polymerase chain reaction (PCR), electrophoresis at 1% agarose and DNA sequence data analysis. The DNA sequence of K. x laetivirens GAPDH gene obtained were 1107 bp and predicted to consist of 5 exons and 5 introns. This sequence had about 68.96%-73.81% similarity to the DNA sequence of the GAPDH gene in several plant species. The amino acid sequence of K. x laetivirens GAPDH had 5 conserved regions and residues of cysteine (C) and histidine. The sequence obtained in this study was the first to be reported from the genus Kalanchoe. This sequence can be used for analysis of gene expression in K. x laetivirens and can be as reference for isolating the GAPDH gene for other plant species in the genus Kalanchoe.